Antimony in lung, liver and kidney tissue from deceased smelter workers. - Gerhardsson, Lars; Brune, D.; Nordberg, Gunnar F.; Wester, P. O. (Scandinavian Journal of Work, Environment & Health, 1982)
Tissue concentrations of antimony in lung, liver, and kidney tissue from a group of deceased smelter workers from northern Sweden have been compared with those of a group of persons without occupational exposure from a nearby area. Neutron activation analysis was used to determine the antimony concentration of lung tissue from exposed workers; these concentrations were 12-fold higher than those of referents (p less than 0.001). For lung tissue there was no tendency towards decreased antimony concentrations with time (up to 20 a) after the cessation of exposure, and this result indicates a long biological half-time. The highest values were found for workers who had worked for many years at the roasters and in the arsenic and selenium departments. There was no significant difference between the antimony concentration of the lung tissue from workers who had died of lung cancer and those of persons who died of other malignancies, cardiovascular disease, or other causes. This finding does not however rule out the possibility of a role for antimony in the etiology of lung cancer among smelter workers since multiple factors may have been operating. The antimony concentration of the liver tissue and the kidney cortex did not differ from the corresponding values of the reference group; this finding indicates either a short biological half-time or insignificance for the systemic distribution of antimony.